The Rise of the English Novel: Defoe, Richardson, and Fielding’s Contributions (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper examines the early formation of the English novel in the eighteenth century by analyzing the significant roles played by Daniel Defoe, Samuel Richardson, and Henry Fielding. These writers laid the groundwork for a new literary genre, shaping its narrative techniques, thematic concerns, and stylistic features. Defoe contributed a sense of realism rooted in everyday life and practical experience, Richardson deepened the novel’s emotional and psychological dimensions through the epistolary style, and Fielding broadened its scope with his comic narrative voice and sharp social commentary. Collectively, their innovations marked a major transition in English literature from classical forms like the romance and epic to a more realistic, character-centered, and socially reflective type of prose.